Cement Roof Tiles - Chaturvedi, M. D. (Indian Forester, 1943)
Cement tiles as a roofing material for forest buildings compel consideration for their strength, neat appearance lightness and above all economy. Made as they are, on the spot the saving effected in transport costs is not inconsiderable. The mixture recommended is sand 3 to cement 1. No reinforcement is required. Machines of various types are available in the market. For curing tiles, complete immersion under water yields best results. Attractive colour schemes could be introduced as desired. The cost at the present high rates amounts to about Rs. 10 per 100 sq. ft. of roof covered.